New findings on the impact of the idealization of corrosion on the brittle failure of steel - Biglu, Michael; von Bock und Polach, Rüdiger Ulrich Franz; Ehlers, Sören (American Society of Mechanical Engineers, 2022)
Corrosion is mostly considered as homogeneous thickness reduction in construction guidelines of the maritime industry. Several studies concluded that besides a homogeneous thickness reduction the corroded non-uniform surface morphology is affecting the strength and strain behavior of steel. However, the effects of non-uniform corrosion on the behavior of steel is still not clearly assessed. The effects of corrosion on the local behavior of steel structures under tensile loading were investigated by conducting tensile tests on naturally corroded steel specimens and analyzing the surface morphology based on surface scans. Influences of geometrical parameters on the strength and strains were determined by carrying out a correlation analysis combined with a Particle Swarm Optimization. Then a non-linear finite element analysis was performed to compare a homogeneous idealization with finite element models considering the naturally corroded surface morphology. Both independent approaches conclude that non-uniform corrosion leads to a more brittle stress-strain behavior of steel compared to a homogeneous corrosion approach, including higher stresses and decreased total breaking strain. In addition we can confirm that pittings and surface roughness are leading to a decrease of the total breaking strain. In contrast to many other studies we highlighted that instead of the pitting corrosion in general, the volume or thickness loss are the primary driver for the ultimate tensile strength reduction.